Causality between White Pepper and Black Pepper: Evidence from Six Markets in Sarawak - Lau, Evan; Puah, Chin-Hong; Oh, Swee-Ling; Lo, Yan-Ching (Munich Personal RePEc Archive (MPRA), 2008)
The study of various spatial price relationships is indeed crucial and has been greatly sought after. Likewise, this study is rather a debatable topic these days especially towards the pricing activity and competitiveness within the pepper industry. Evidence from six markets within Sarawak had found that a long run relationship between the pepper markets does actually exist. And using the MWALD test though, findings revealed that the white pepper prices do Granger cause the black pepper prices in all divisions. However, there is no indication of causality that runs from the black pepper towards the white pepper. In other words, white pepper does affect the black pepper, but not the other way around. Due to the integration within the pepper industry, thus, excess profit making opportunity will not be made beneficial as the pepper markets are efficient.